Folkmord historien om ett brott mot mänskligheten - Karlsson, Klas-Göran 1955- (Historiska Media, 2021)
The genocide in Rwanda in 1994. The Nazi annihilation of Jews in Europe during World War II. Communist regime abuses against its own peoples in Russia and the Soviet Union from 1918, in China from 1949 and in Cambodia 1975-1979. In this book, the reader gets an in-depth, historical perspective that goes all the way back to antiquity, but with a special focus on mass murder in modern times. It was during the 20th century that new technical, bureaucratic and ideological developments made possible large-scale abuses. The description follows three main tracks. The first is traditionally historical and is linked to individual genocides - their causes and effects, intentions and actual results. The second addresses the general conditions for this crime in a "genocidal society", societies marked by murderous ideologies, strong social tensions and threats based on war and revolution. The third is retrospective and highlights consequences in history
Keywords: Geschichte; Völkermord; Genocide / History; Crimes against humanity; Crimes contre l'humanité; Genocide; History